2021
DOI: 10.1183/16000617.0076-2021
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics and sarcoidosis

Abstract: Epigenetic modifications are emerging as important regulatory mechanisms of gene expression in lung disease, given that they are influenced by environmental exposures and genetic variants, and that they regulate immune and fibrotic processes. In this review, we introduce these concepts with a focus on the study of DNA methylation and histone modifications and discuss how they have been applied to lung disease, and how they can be applied to sarcoidosis. This information has implications for other exposure and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 149 publications
0
4
0
Order By: Relevance
“…The generally accepted hypothesis states that the formation of the sarcoid granulomas results from a response to so far unknown foreign antigen/pathogen. It is supported by other granulomatous diseases with known aetiological agents, such as tuberculosis, chronic beryllium diseases or occupational diseases [48][49][50].…”
Section: Pathophysiology Of Pulmonary Sarcoidosismentioning
confidence: 99%
“…The generally accepted hypothesis states that the formation of the sarcoid granulomas results from a response to so far unknown foreign antigen/pathogen. It is supported by other granulomatous diseases with known aetiological agents, such as tuberculosis, chronic beryllium diseases or occupational diseases [48][49][50].…”
Section: Pathophysiology Of Pulmonary Sarcoidosismentioning
confidence: 99%
“…The most comprehensively studied epigenetic modification is the addition of a methyl group to cytosines next to guanines in the DNA molecule ( i.e. DNA methylation in CpG sites), but modifications of histone tails, non-coding RNAs such as microRNAs and long non-coding RNAs are also part of the epigenetic processes [ 107 109 ]. Epigenetic modifications have not yet been explored in bronchiectasis, but COPD studies have shown that mild-to-moderate COPD presents a smoking-related epigenetic signature that is absent in severe COPD [ 110 ], and recent studies have identified some shared epigenetics differences between blood and lung [ 111 ].…”
Section: From Pathophysiology To Multiomicsmentioning
confidence: 99%
“…However, 30% of patients still develop a chronic course, and persistent granulomatous in ammation may lead to irreversible pulmonary brosis (PF) [11][12][13][14]. The occurrence and development process of brotic pulmonary sarcoidosis (FPS) is very complex [15], and its pathogenesis is not yet clear, lacking effective treatment methods [16]. The prognosis of FPS primarily depends on the degree of brosis, severity of functional impairment, and the development of pulmonary hypertension (PH), along with the in uence of various complications [17][18][19].…”
Section: Introductionmentioning
confidence: 99%